2016
DOI: 10.1080/00981389.2016.1199454
|View full text |Cite
|
Sign up to set email alerts
|

Young women’s sexual involvement in emerging adulthood

Abstract: Using data from the Relationship Dynamics and Social Life Study, this study examined the association of peer, family, attitudinal, aspirational, and attainment factors relevant to 820 young women’s (aged 18–19) number of sexual partners. Overall, this study found that perceived peer norms and early onset of sexual initiation had a positive and statistically significant association with the respondents’ number of lifetime sexual partners. While high school performance and college aspirations were inversely asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
(86 reference statements)
0
3
1
Order By: Relevance
“…Most participants self-identified as heterosexual ( n = 255, 70.06%), followed by bisexual ( n = 83, 22.8%), homosexual ( n = 7, 1.9%), and other (queer, pansexual, asexual, or undefined; n = 15, 4.1%). The proportion of sexual minorities in the current sample was greater than recent population estimates of women living in developed nations (Wilson & Shalley, 2018), although not unusual, given sexual fluidity and experimentation are often heightened in emerging adult cohorts (Paat & Markham, 2016). Most participants were currently in an exclusive relationship ( n = 256, 70.9%) and had completed a university degree ( n = 175, 48.1%).…”
Section: Methodscontrasting
confidence: 62%
See 1 more Smart Citation
“…Most participants self-identified as heterosexual ( n = 255, 70.06%), followed by bisexual ( n = 83, 22.8%), homosexual ( n = 7, 1.9%), and other (queer, pansexual, asexual, or undefined; n = 15, 4.1%). The proportion of sexual minorities in the current sample was greater than recent population estimates of women living in developed nations (Wilson & Shalley, 2018), although not unusual, given sexual fluidity and experimentation are often heightened in emerging adult cohorts (Paat & Markham, 2016). Most participants were currently in an exclusive relationship ( n = 256, 70.9%) and had completed a university degree ( n = 175, 48.1%).…”
Section: Methodscontrasting
confidence: 62%
“…Women are also significantly more likely than men to be at risk of sexual abuse and other forms of sexual victimization (Australian Institute of Health and Welfare [AIHW], 2018; Mellins et al, 2017). Furthermore, young women are negotiating the developmental period of emerging adulthood (Arnett, 2011), which is associated with heightened sexual activity, sexual experimentation, and sexual risk-taking behavior (Paat & Markham, 2016), and may increase their vulnerability to experiencing NCCR.…”
Section: Introductionmentioning
confidence: 99%
“…The use of alcohol also acts as an indicator of sexual risk due to a mechanism of collateral action which can result in a decrease and impairment in perception and control by the adolescent to undergo sexual experiences. 5 , 6 The lack of using condoms and the higher number of sexual partners is considered at-risk sexual behaviors which have the occurrence of sexually transmitted diseases (STDs) and unplanned pregnancies among their consequences. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Many studies have suggested that this behavior is influenced by determinants like age, gender, level and stream of education and socioeconomic status [23,24]. It is interesting to note that poor attitude, knowledge/awareness and risky practices related to STIs are a universal phenomenon in the young adulthood [7], with females having higher risk of contracting an STD than their male peers due to differences in biology, sexual behavior, social attitudes, peer pressures, economic states and vulnerability.…”
Section: Introductionmentioning
confidence: 99%